THE IMPACT OF SPORT ON THE QUALITY OF LIFE AMONG CHILDREN AND ADOLESCENTS - Alexandru-Ilie Tudurache; Diana Elena Lazar; Roxana Postolica; Mihai Lucian Ciuntea (Sport şi Societate)
This article aims to review the literature on the relevance of sport in children and adolescents and its impact on the quality of life. Currently, quality of life is an essential topic of research in various fields, but studies point out that it is often mistaken for the standard of living or level of health. Sport is an important activity that helps physical andmental development, as shown by the findings of studies among children and adolescents. Based on the results of the studies, meta-analyses and systematic reviews assessed and included in this article, it has been shown that playing sports has significant effects on the psychological, social, and physical well-being and the functioning of the school environment. Upon using the following keywords ("quality of life" OR ("quality" AND "life") OR "quality of life") AND ("sport s" OR "sports" OR "sports" OR "sport" OR "sporting") AND ("child" OR "child" OR "children" OR "child s" OR "children s" OR "children’s" OR "child’s") AND ("adolescences" OR "adolescency" OR "adolescent" OR "adolescent" OR "adolescence" OR "adolescents" OR "adolescent s") AND ("Romania" OR "România" OR "Romania s") we conducted a search on PubMed for the studies published on the quality of life among Romanian children and adolescents who practice sports but found no results published so far on this research topic, which leads us to believe that initiating research studies on the impact of sports activities on quality of life in Romania would bring significant benefits, especially for children and adolescents.